What Is the Role of Quality Management Systems for AI Devices? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Artificial intelligence (AI) is no longer a futuristic concept in healthcare; it is a present-day reality, with AI-powered medical devices transforming diagn...
Keywords: FDA Regulation and Compliance; Quality; Management; Systems; Artificial Intelligence; Healthcare; Diagnostics